Prospective evaluation of surgical management of sliding hiatal hernia and gastroesophageal reflux in dogs. Issue 8 (1st November 2017) - Mayhew, Philipp D.; Marks, Stanley L.; Pollard, Rachel; Culp, William T. N.; Kass, Philip H.
Abstract: Objective: To evaluate response to surgical management of sliding hiatal hernia (SHH) and gastroesophageal reflux (GER) in dogs using standardized clinical scoring, videofluoroscopic swallow studies, and impedance planimetry. Study design: Prospective clinical trial. Animals: A total of 17 client‐owned dogs. Methods: Dogs were included if they had clinical signs and videofluoroscopic evidence of SHH and/or GER. Owners were asked to complete a standardized canine dysphagia assessment tool (CDAT) preoperatively and postoperatively. Conscious videofluoroscopic swallowing studies and impedance planimetry (IP) were used to evaluate esophageal function and lower esophageal sphincter location and geometry preoperatively and in a subsection of dogs postoperatively. Results: Preoperatively, 13/17 dogs included in the study had a history of regurgitation, and 4/17 had radiographic evidence of aspiration pneumonia. Postprandial regurgitation improved in 8/10 dogs with preoperative regurgitation, and for which completed preoperative and postoperative CDAT questionnaires were available ( P < .01). The hiatal hernia severity score improved postoperatively ( P = .046) in dogs with preoperative and postoperative videofluoroscopic swallowing studies (n = 12). However, hernia frequency score ( P = .2) and IP parameters did not differ significantly between time points. Conclusion: Clinical signs of SHH generally improved with surgery but did not consistently resolve. Videofluoroscopic studies provide evidence that GER and SHH can persist postoperatively in some patients. Based on IP findings, clinical improvement may be attributed to a mechanism independent of lower esophageal sphincter attenuation.